Cardiac resynchronization therapy reverses severe dyspnea associated with acceleration‐dependent left bundle branch block in a patient with structurally normal heart. (11th January 2019) - Prystowsky, Eric N.; Padanilam, Benzy J.
Abstract: A 55‐year‐old woman presented with severe dyspnea during acceleration‐dependent left bundle branch block (LBBB). Metoprolol initially ameliorated symptoms by preventing the heart rate at which LBBB occurred. Over time LBBB presented at slower heart rates and the patient developed recurrent dyspnea during an activity that correlated with the development of LBBB on event monitors and exercise stress testing. A biventricular pacemaker was implanted, and the patient's symptoms remain resolved after a follow‐up of over 4 years. More research is needed to define the use of cardiac resynchronization therapy in patients with normal heart function.